Star trek VI : the undiscovered country [videorecording (Blu-Ray)] - Meyer, Nicholas, 1945-; Winter, Ralph, 1952-; Jaffe, Steven-Charles; Shatner, William; Nimoy, Leonard; Kelley, DeForest, 1920-1999; Konner, Lawrence; Cattrall, Kim; Warner, David, 1941-2022; Plummer, Christopher; Doohan, James; Koenig, Walter; et al. (Star Trek (Motion picture), 2009)
After a lunar cataclysm brings the Klingon Empire to its knees, the foreign concept of peace with the Federation may be finally within reach, but ironically, it is Kirk who is the first emissary to broker that peace, but Kirk and his crew are implicated in the brutal assassination of a Klingon diplomat, bringing both worlds to the brink of full-scale war.